Transitions from vocational to higher education: policy context and practice in England - Ertl, Hubert [Verfasser]; Hayward, Geoff [Verfasser]; Katartzi, Eugenia [Verfasser] (My University, 2019)
"This contribution analyses the transition landscape between vocational and higher education in England. It discusses the policy context that frames transitions between the two educational sectors and sets out how students from vocational pathways can potentially contribute to the aims of the widening participation agenda in England. The contribution builds on data collected by a TLRP (Teaching and Learning Research Programme)/ESRC (Economic and Social Research)-funded project on transitions from vocational to higher education and also discusses recent data on progression of different educational pathways into higher education and the labour market. The analysis explores some of the frictions students with vocational background experience when studying for a higher education degree as well as the support they require in order to succeed. The paper argues that evenly-distributed access to higher education for students with vocational qualifications has not been achieved, posing questions for the wider societal role of higher education institutions but also regarding the efficiency of widening participation policies." (authors' abstract; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.4 Hochschulbildung; I 2.2.1 Westeuropa; Berufsbildung; Hochschulbildung; Durchlässigkeit im Bildungssystem; Nicht traditionell Studierender; Berufsbildungspolitik; England